The Urgency of Defense Diplomacy in Preventing the Threat of Drug Trafficking in Indonesia - M. Rinaldi; Rodon Pedrason; Muhammad Hadianto Wirajuda (Jurnal Kewarganegaraan, 2023)
Abstract Drug trafficking has become a serious threat to Indonesia's security. As a country with a strategic geographical position, Indonesia has become a target for international drug trafficking groups. The Indonesian government recognizes the urgency and negative impact that drug trafficking has on society. Defense diplomacy is one approach that can be used to overcome the threat of drug traffickingThe method used in this research is a qualitative descriptive method. The descriptive method uses a qualitative approach, namely research that intends to understand the phenomenon of what the research subject experiences, namely the Urgency of Defense Diplomacy in Preventing the Threat of Drug Trafficking in Indonesia. Defense diplomacy plays an important role in efforts to prevent the circulation of drug threats in Indonesia. In addition, defense diplomacy can also be used to strengthen cooperation in the field of research and development in order to identify and deal with new types of drugs that continue to grow. By collaborating with partner countries, Indonesia can accelerate the discovery of innovative technologies and methods in drug prevention, testing and handling. It can be concluded that defense diplomacy plays an important role in preventing and countering drug trafficking in Indonesia. Defense diplomacy can be an effective approach in addressing the threat of drug trafficking through international cooperation. Defense diplomacy involves various aspects, including military and non-military aspects, with the aim of building cooperation, strengthening bilateral relations, and promoting national interests in drug trafficking prevention efforts. Keywords: Defense Diplomacy, Drug Trafficking, Drug Prevention